Active search screening for oral potentially malignant disorders and oral cancer in the city of Piracicaba - Matheus Ferreira LINARES; Silvia Maria Paparotto LOPES; Adriana Eliza Brasil MOREIRA; Pablo Agustin VARGAS; Alan Roger dos Santos SILVA; Márcio Ajudarte LOPES (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract Oral cancer is a public health problem worldwide with approximately 300,000 new cases diagnosed every year and more than 170,000 deaths annually. Squamous cell carcinoma (SCC) accounts for approximately 90% of all oral malignancies and it is frequently preceded by lesions known as oral potentially malignant disorders (OPMDs). Screening programs for early detection of oral lesions have been conducted. Therefore, the objective of this research was to carry out an active search in a screening program in the city of Piracicaba, Brazil. High-risk patients were identified at the city's health center through their medical records and referred for dental consultation. Other patients who opportunistically sought dental care were also seen and if they did not present risk factors for SCC, they were considered low-risk. A total of 756 patients were examined, and 445 met the criteria for the high-risk group and 311 for the low-risk group. It was possible to diagnose 27 OPMDs and six SCCs - 21 OPMDs and six SCCs occurred in high-risk patients and six OPMDs in low-risk patients. A chi-square test was applied and a statistically significant value (p = 0.006) was obtained for the detection of OPMD and SCC in patients of the high-risk group. Screening of high-risk patients through active search proved to be an effective program for diagnosing OPMD and SCC. Therefore, we encourage its implementation on a large scale to reduce the current scenario of this disease.